Chorologie novelties for the Central-Spain flora - Castillo, Juan Luis; Carrasco de Salazar, María Andrea (Botanica Complutensis, 1993)
CARRASCO MA. & CAsríLLo IL., 1993. Sume new taxa trom Central Spain. Bot. Complutensis IB: 255-258 This paper síates seven taxa of vascular plants collected in Toledo province, Spain. AII of Ihem are lirst records lor Toledo province, being three of them: Evax lusitanica Samp., Romulea ramifiora Ten. subsp. ramiflora and Orchis patens Desf, new records for bigger arcas. Dala about water eharacteristie are presented loo in relation with Ranuneulus peltatus Schrank subsp. pelíatus.